The Effectiveness of the Implementation of the Death Penalty for Suspects in Serious Crime Cases, Both Narcotics and Corruption in order to reduce Corruption and Narcotics Cases that Occur in Indonesia for the Advancement of the Nation and the State (Universitas Negeri Semarang, 2021)
Corruption has become a serious disease in this country and is very difficult to cure. Various efforts to prevent and eliminate corrupt practices have been carried out very often. Both with the formation of laws and regulations as well as the establishment of a commission or agency for the prevention of corruption. However, corruption never wants to leave the Indonesian people. There is corruption in the executive branch, as well as in the legislature and judiciary. Not to mention in several state-owned enterprises and non-ministerial state institutions. The phenomenon of corruption has made people hot and angry. Because the perpetrators of corruption have taken people's rights by force. However, law enforcement against the perpetrators is not going well. Most of the criminals are given light sentences. However, the law provides for the death penalty for the perpetrators. The community hopes that the perpetrators of corruption are punished with the severest severity, so that justice and public welfare can be fulfilled.